(untitled) (Jurnal Bahasa, 2018)
The study aims to identify and describe the meaning of anthropomorphism elements used by the speakers (especially the subgroups) during the process of greeting or calling someone while communicating. The research data were drawn from six local films with the theme of social issues which presumably represent the communication process of the lower class society. Data which have been identified were analyzed using the three-step process model introduced by Stöver, a model that describes how the understanding of a word can be explained in a reasonable and empirical manner. Findings reveal that the speakers employ three animal symbols as anthropomorphism elements such as dogs, chickens and insects (ants, lice and the bluebottle flies). It is believed that the selection of the three animals did not occur arbitrarily; instead it is motivated as it is connected with the human cognitive system that quickly searches for the similarities between animal and human traits. Keywords: anthropomorphism, three step process model, animal trait, human trait, simulation process